Isoflurane and the Analgesic Effect of Acupuncture and Electroacupuncture in an Animal Model of Neuropathic Pain - Lauren N. Spezia Adachi; Rafael Vercelino; Carla de Oliveira; Vanessa L. Scarabelot; Andressa de Souza; Liciane F. Medeiros; Stefania G. Cioato; Wolnei Caumo; Iraci L.S. Torres (Medical Association of Pharmacopuncture Institute, 2018)
The present study aimed to determine whether isoflurane interferes with the analgesic effects of acupuncture (Ac) and electroacupuncture (EA), using a neuropathic pain (NP) rat model. In total, 140 male Wistar rats were used; isoflurane-induced nociceptive response was evaluated using the von Frey test, serum calcium-binding protein β (S100β) levels and nerve growth factor (NGF) levels in the left sciatic nerve. The NP model was induced by chronic constriction injury of the sciatic nerve at 14 days after surgery. Treatment was initiated after NP induction with or without isoflurane anesthesia (20 min/day/8 days). The von Frey test was performed at baseline, 14 days postoperatively, and immediately, 24 h, and 48 h after the last treatment. Results of the nociceptive test and three-way analysis of variance were analyzed by generalized estimating equations, the Bonferroni test, followed by Student-Newman-Keuls or Fisher's least significant difference tests for comparing biochemical parameters (significance defined as p ≤ 0.05). At baseline, no difference was noted in the nociceptive response threshold among all groups. Fourteen days after surgery, compared with other groups, NP groups showed a decreased pain threshold, confirming establishment of NP. Ac and EA enhanced the mechanical pain threshold immediately after the last session in the NP groups, without anesthesia. Isoflurane administration caused increased nociceptive threshold in all groups, and this effect persisted for 48 h after the last treatment. There was an interaction between the independent variables: pain, treatments, and anesthesia in serum S100β levels and NGF levels in the left sciatic nerve. Isoflurane enhanced the analgesic effects of Ac and EA and altered serum S100β and left sciatic nerve NGF levels in rats with NP. Keywords: acupuncture, electroacupuncture, isoflurane, neuropathic pain